(untitled) (Eurasian Medical Research Periodical, 2022)
Analysis of destructive tendencies in the structure of adolescent depressive behavioral disorders determined that adolescents more often experience demonstrative-blackmail suicidal behavior, which is formed against the background of depressive affect, as a result of intrapersonal conflicts and is mainly a problem of behavioral and stress-related disorders that arise against the background of psychopathological states of nonpsychotic level. The study of the clinical features of self-destructive actions in adolescents with behavioral disorders of the depressive register allows us to identify risk groups for suicidal readiness among this contingent of patients.